KELEMBAGAAN PENGELOLAAN SUMBERDAYA LAHAN DI PESISIR KABUPATEN SIDOARJO - Slamet Subari (MediaTrend, 2009)
So far, the guideline of the government of Sidoarjo Regency in managing coastal area regulated in the Land use Planning (RTRW) of Sidoarjo Regency has not been effective yet. This research aims at studying the cause factors of the ineffective implemention of the Land use Planning of the year 2002-2011. The institutional analysis was used in this research by applying some approaches, beside agency theory, transaction cost theory and organizational form choices theory were applied in this research.From the discussion, it can be concluded that the implementation of the Land use Planning of the year 2002-2011 will potentially increase the District Original Revenue (PAD) till RP.2,327329977. This value has not been sufficient yet to give compensation for the farmers who suffer the lost because of the shift of land use pattern as a result of the implementation of the Land use Planning. The enhancement of District Original Revenue makes more difficult to cover transaction cost for organizational governance to enforce the Local Regulation (Perda) on Land use Planning of the year 2002-2011. As the consequence, to implement Local Regulation (Perda) on Land use Planning of the year 2002-2011 is difficult.